Evaluasi Program Praktik Kerja Lapangan Jurusan Tata Boga Politeknik Negeri Balikpapan - Tuatul Mahfud (Jurnal Pendidikan Teknologi dan Kejuruan, 2016)
The objective of this study is to evaluate the implementation of on the job training program in the Department of Cookery of Balikpapan State Polytechnic in terms of its relevance with the practical courses, the role of the program to improve the students' skills and the job descriptions of the program. This study is descriptive quantitative. The subjects of this study were 37 students of the Department of Cookery, Balikpapan State Polytechnic. The data collection techniques used questionnaires, interviews and documentations. The data analysis method used descriptive statistics. The results of the study revealed most of the students agree that the practical courses are relevant with the needs of the job training program with the mean scores of 4.2, the program improves the students’ skills with the mean scores of 4.3, the specific works assigned are related to their field of study with the mean scores of 4.1 and most of the students are responsible for preparing guests’ order with the mean scores of 4,0.